Optimization and evaluation of a method for the generation of DNA barcodes for the identification of crustaceans. (November 2016) - Eischeid, Anne C.; Stadig, Sarah R.; Handy, Sara M.; Fry, Frederick S.; Deeds, Jonathan
Abstract: Efficient methods for the species identification of seafood are important for ensuring food safety and detecting fraud. DNA barcoding, a technique based on PCR amplification and capillary sequencing of a short, standardized segment of a gene, is a reliable method for species identification of processed and packaged seafood when the species cannot be determined visually. Here we report the optimization and evaluation of a DNA barcoding method for identifying representative commercial decapod crustacean species, including select shrimp, crab, crayfish, and lobster. Two different segments of the mitochondrial cytochrome c oxidase 1 (COI) gene were evaluated —a 655 base pair fragment beginning near the 5′ end, representing the "standard" DNA barcode fragment, and a non-overlapping 475 base pair fragment beginning near the 3′ end, representing an alternative DNA barcode marker for shrimp. The standard 5′ fragment was successfully amplified and sufficient to identify most crustacean species tested, but amplification of both the 5′ and 3′ barcodes were often required to efficiently identify shrimp. Highlights: 5′ COI DNA barcoding differentiates most crustaceans but is not optimal for shrimp. 3′ COI DNA barcoding can be used to differentiate shrimp species. PCR optimization is important for successful COI DNA barcoding of crustaceans.